مقاصد الشريعة في صلة الأرحام والواقع المعاصر : دراسة شرعية تحليلية - هزازي، صالح فاضل عبد الرحمن (Kulliyat Ma'arif al-Wahy wa-al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah, 2011)
This study deals with an aspect of our social relationships that is of significant importance in our daily lives, by studying Quranic verses and authentic Ahadith with the aim of extracting the Shari'ah objectives that are related to kinship ties. The study examines the problem of kinship ties between the societal perspective that restricts it to a single sermonic dimension and its true position in Islamic Shari'ah. The study relies on inductive analytical methodology that leads to a number of results, the most important of which are considering the inductive methodology as the most important method for exposing the objectives of Shari'ah, while taking into account the development of Maqasidi Ijtihad in tandem with the development of society and its needs. The study shows the position of maintaining kinship ties in many Maqasidi classifications, and the study is of the opinion that the Maqasidi level of maintaining kinship ties is governed by the needs of the society. Thus, it becomes a necessity in a society where cooperation between individuals exists only between relatives, and where life is impossible without them. On the other hand, kinship ties becomes a need in a society where an individual lives with great difficulty without relying on the help of relatives. As for the society where the state takes care of every individual, and as such they do not need help from anyone including their relatives, then maintaining kinship becomes desirable. The study reaches the conclusion that the most important objective of Shari'ah in regards to maintaining kinship ties is mending relations, protecting the family and maintaining the unity of Muslims. The study divides kinship into three groups, mainly unmarriageable kinship such as parents, marriageable kinship such as cousins, and kinship that is the result of a relationship by marriage or breastfeeding. The study notices the agreement amang jurists on the obligation of maintaining kinship, and their disagreement regarding the scope of such obligation, which the study limits to the first group of lineage kinship. The study also talks about the most important reasons that can lead to severing the ties of kinship, and the most important remedies for such reasons.